THE ROLE OF TEACHERS IN INCREASING STUDENTS' PAI LEARNING MOTIVATION AT MADRASAH - Maisuroh, Siti; Jamil, Moh.; Hasanah, Lutfiatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to investigate and analyze the role of teachers in enhancing the motivation to learn Islamic Religious Education (PAI) in Madrasah Ibtidaiyah Negeri 1 Probolinggo. Islamic Religious Education plays a central role in shaping the character and morals of students, and learning motivation is a key factor in achieving these objectives. The research method employs a qualitative approach through in-depth interviews with a number of PAI teachers in the madrasah. The interview results are analyzed to identify the best strategies and practices used by teachers in enhancing PAI learning motivation. The research findings indicate that teachers play a crucial role in creating a motivating learning environment for students. Strategies employed by teachers include the use of innovative teaching methods, integration of technology, and a deep understanding of the individual needs of students. Additionally, teachers establish close collaborations with parents to provide additional support. The results of this research can serve as a guide for teachers, school principals, and relevant stakeholders in developing policies and programs aimed at improving PAI learning motivation at the elementary madrasah level. By understanding the key role of teachers in PAI learning motivation, it is hoped that the madrasah can create a more optimal learning environment, providing a positive impact on the spiritual and academic development of students